ENGLISH STUDENTS PERCEPTION ON THE USE OF WHATSAPP GROUP IN SPEAKING CLASS - Meiga Ratih Tirtanawati; Dhiana Shilvina Salsabila (Institut Agama Islam Negeri (IAIN) Manado, 2021)
Online learning is a new policy from the minister of education and culture in the midst of the covid-19 pandemic. It is the first time for english students in IKIP PGRI Bojonegoro do the online learning in speaking class. Speaking is one of the important skills learned in english language. In this era the technology is developing rapidly. Many applications that can support online learning, One of them is whatsapp. Whatsapp is a simple, secure, and reliable messaging application. This research discuss about students’ perception on the use of whatsapp group in speaking class. The study aim to find out english students perception on the use of whatsapp group in speaking class and to find out english students challenges on the use of whatsapp group in speaking class. This research includes qualitative research with descriptive qualitative. The participant of this research was 35 students of the thirth semester of English Education Department academic year of 2020/2021 in IKIP PGRI Bojonegoro. The techniques of collecting data are interview, questionnaire and documentation. In this research researcher analyzed data by data reduction, data display and drawing conclusions. The result show that students perception on the use of whatsapp group in speaking class is less interesting and less effective. Their challenges on the use of whatsapp group are internet connection, feeling bored and lazy, difficult to understand the materials and the time is not according to the schedule. online learning using whatsapp group in speaking class needs more interesting learning activity.